1995
DOI: 10.1016/0014-5793(95)00183-a
|View full text |Cite
|
Sign up to set email alerts
|

Purification of an NADPH‐dependent diaphorase from membrane of DMSO‐induced differentiated human promyelocytic leukemia HL‐60 cells

Abstract: NADPH diaphorase activity was found in membrane of DMSO-induced differentiated human promyelocytic leukemia HL-60 cells. This membrane-bound diaphorase activity increased dramatically during differentiation of HL-60 ceils. A dye reductase was extracted from membrane of DMSO-induced differentiated HL-60 cells with n-octyl glucoside and sodium cholate in the presence of several protease inhibitors such as PMSF, DIFP, TLCK, aotipain, chymostatin, leupeptin, pepstatin A and trypsin inhibitor. The NADPH diaphorase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…7 The gels were incubated at 37°C for 30 min in the reaction mixture (0.4 mM NADPH, 8 mM MgCl 2 , 0.5 mM piodonitrotetrazolium violet and 10% glycerol in 50 mM phosphate buffer (pH 7.0)). 8 The incubation was stopped by washing in ice-cold buffer (50 mM phosphate buffer, pH 7.0).…”
Section: Nadph-diaphorase Activity Staining and Western Blot Analysismentioning
confidence: 99%
“…7 The gels were incubated at 37°C for 30 min in the reaction mixture (0.4 mM NADPH, 8 mM MgCl 2 , 0.5 mM piodonitrotetrazolium violet and 10% glycerol in 50 mM phosphate buffer (pH 7.0)). 8 The incubation was stopped by washing in ice-cold buffer (50 mM phosphate buffer, pH 7.0).…”
Section: Nadph-diaphorase Activity Staining and Western Blot Analysismentioning
confidence: 99%
“…Isolated rat hepatocytes in culture show all signs of rapid dedifferentiation together with the translocation of ZnBP into the nucleus. But this relationship is more than circumstantial as indicated by the fact that DMSO not only inhibits dedifferentiation of hepatocytes (Ai et al, 1995;Kuliczkowski et al, 1995;Otsuka-Murakami and Nishimoto, 1995), but also abolishes completely over a long time the translocation of ZnBP from the cytoplasm to the nucleus. It should also be noted, that the amount of ZnBP in human breast cancer is dramatically increased (Tsitsiloni et al, 1998), an observation we could confirm for hepatocarcinoma cells (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that an additional flavin containing dehydrogenase from rabbit peritoneal neutrophils and pig neutrophils is able to enhance superoxide production in a cell‐free system [10–12]. Nisimoto et al [13, 14]have purified an NADPH‐cytochrome c reductase from human neutrophils and HL‐60 cells but did not observe a marked stimulation of superoxide generation by the purified reductase.…”
Section: Introductionmentioning
confidence: 99%